EFFECTIVENESS OF E-GOVERNMENT IMPLEMENTATION THROUGH ONLINE SERVICES (PLAVON) DUKCAPIL AS A POPULATION DOCUMENT MANAGEMENT APPLICATION IN JATIKALANG VILLAGE - Putmala Sari, Riska; Rodiyah, Isnaini (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the effectiveness of e-government implementation through the Dukcapil Online Service (PLAVON) application in managing population documents in Jatikalang Village. Method: A qualitative descriptive approach was applied, with data collected through interviews, observations, and documentation, and analyzed using the Miles and Huberman interactive model. Results: The findings show that PLAVON has improved the efficiency of population administration services by reducing queues, accelerating document issuance, and enhancing transparency and accountability. Despite these achievements, several challenges remain, including limited community digital literacy, inadequate internet access, and technical difficulties in application use. Socialization and training initiatives conducted by the village government have partially addressed these issues, helping to increase public awareness and usage of the system. Novelty: This research provides new insights by contextualizing the adoption of PLAVON at the village level, highlighting not only its role in improving administrative efficiency but also the socio-technical challenges that must be addressed to ensure inclusivity and sustainability in digital-based public service delivery.